Revision of the endemic Hispaniolan genus Asteriza Chevrolat, 1836, with description of two new species (Coleoptera: Chrysomelidae: Cassidinae: Ischyrosonychini) - Shin, Chulwoo; Chaboo, Caroline S.; Clark, Shawn M. (Zootaxa, 2012)
The cassidine genus Asteriza Chevrolat, 1836 is redescribed and two new species, Asteriza blakeae Shin, Chaboo & Clarkand Asteriza tainosa Shin, Chaboo & Clark, are described from the Dominican Republic. A phylogenetic analysis and anillustrated key to the four Asteriza species are provided. Asteriza blakeae is diagnosed by the reddish lateral margin of thepronotum and more swollen brownish elytral margins. Asteriza tainosa is diagnosed by the relatively swollen maxillary and labial palpi and dominant yellow coloration of the elytra and pronotum.